Anopheles goeldii Rozeboom & Gabaldón (Diptera, Culicidae): a species of the Nuneztovari Complex of Anopheles Meigen - Denise Cristina Sant’Ana (Revista Brasileira de Entomologia, 2015)
Anopheles (Nyssorhynchus) goeldii Rozeboom & Gabaldón, 1941, a species of the Nuneztovari Complex, was described based on morphological characteristics of the male, female, larva, pupa, and eggs. The type locality is Boa Vista (= Fordlândia), a district in the vicinity of Rio Tapajós, in the municipality of Aveiro, in the state of Pará, Brazil. Anopheles goeldii is redescribed based on morphological traits of the fourth instar larva, pupa, egg, and male and female. DNA sequences from the cytochrome oxidase subunit I (COI barcode region) of the mitochondrial genome were utilized for species characterization. Specimens of An. goeldii from the Pará, Amapá, and Amazonas states were employed to redescribe the species and to compare with morphologically similar taxa. Keywords: Adult, Pupa, Fourth instar larva, Scanning electron microscopy eggs, Cytochrome oxidase subunit I barcode, Anopheles nuneztovari